2021
DOI: 10.3390/asi4040092
|View full text |Cite
|
Sign up to set email alerts
|

User eXperience (UX) Evaluation for MR Cultural Applications: The CEMEC Holographic Showcases in European Museums

Abstract: Within the EU CEMEC project framework, a novel approach for using holographic showcases in museums has been conceived and experimented upon in different venues in the context of an itinerant exhibition dealing with Early Medieval European collections. The purpose of this holographic showcase, the so-called “box of stories”, is to improve the link and interaction between real and virtual contents in the museum’s context, making the exhibited object “alive” in the visitors’ perception. An Avar sword and a Byzant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In previous studies about visitors' experiences with holographic showcases [26,29], we observed some common patterns; for example:…”
Section: Comparison With Previous Studies About Showcasesmentioning
confidence: 75%
See 2 more Smart Citations
“…In previous studies about visitors' experiences with holographic showcases [26,29], we observed some common patterns; for example:…”
Section: Comparison With Previous Studies About Showcasesmentioning
confidence: 75%
“…The real and the digital co-exist in the same showcase. During the CEMEC project, we experienced this installation in many European museums with different audiences, collecting several hundreds of pieces of data about its usability and the visitors' reactions [29].…”
Section: The Holographic Showcase: Design Of the Installation And Com...mentioning
confidence: 99%
See 1 more Smart Citation
“…The system developed enables readability and recontextualization of the artifact and the emotional narrative activates the transfer of knowledge to visitors [38].…”
Section: Supporting the Interpretation Of Objects In The Exhibition S...mentioning
confidence: 99%
“…As in the case of the European CEMEC project (2015-2019), a collaboration between universities, museums, and technical partners led to the development and evaluation of holographic showcases to promote Early Medieval arts and cultures across Europe. A traveling exhibition showed the holographic showcase's impact on the public, emphasizing a coherent communication ecosystem integrating real and digital contents, narrative approaches, and scalability [11].…”
Section: Introductionmentioning
confidence: 99%